Disarmament is the New War, Gold is the New Opium, and Ecohealth is the Historic Victim. (July 2019) - Villar, David; Schaeffer, David J
In Colombia, the convergence of drug trafficking, illegal armed groups, and gold production and trade threatens peace and stability in the post-FARC (Revolutionary Armed Forces of Colombia) era, as had the narcotics trade previously. Armed groups and criminal organizations have increased and consolidated their influence over illegal mining and may be diverting US5 billion from Colombia's annual economy. As of 2014, 46% of the total area (78 939 ha) exploited for alluvial gold was in the Afro-Colombian Pacific States, in which unregulated mining was the main driver of deforestation. The informal job market represents 49% of the workforce and absent other economic alternatives, this workforce of ex-guerrillas, organized crime groups and corrupt officials will sustain the black markets that permeate gold mining. Human health consequences of unregulated gold mining are largely unrecognized, but include the spread of malaria and other insect-borne diseases, and we suggest diseases such as babesiosis.